2017
DOI: 10.5301/tj.5000655
|View full text |Cite
|
Sign up to set email alerts
|

Winners' Cup: A National Football Tournament Brings Together Adolescent Patients with Cancer from all over Italy

Abstract: Società Scientifiche Italiane Insieme per gli Adolescenti con Malattie Onco-ematologiche (SIAMO) is an Italian nationwide scheme that focuses on adolescent patients with cancer. Some of its activities include promoting dedicated local projects at the various oncology centers all over the country and organizing events to improve awareness regarding cancer in adolescence. It is with these aims in mind that it organized the Winners' Cup, a football tournament between Italian adolescents who had (or had had) pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…and ''Get a check-up'') to help young people to interpret any symptoms they experience, seek medical advice, and arrive at an earlier diagnosis), 31 and the ''Winners' Cup'' (a football tournament for adolescents with cancer, or a history of cancer; in its third edition in 2019, young people from eight different European countries were involved). 32 Although some such initiatives proved successful, others were less so. A national project called SIAMO (Società Italiana Adolescenti con Malattie Onco-ematologiche [Italian Society for Adolescents with Oncohematological Diseases]) was launched in 2014, 33,34 as an extension of the AIEOP Committee on Adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…and ''Get a check-up'') to help young people to interpret any symptoms they experience, seek medical advice, and arrive at an earlier diagnosis), 31 and the ''Winners' Cup'' (a football tournament for adolescents with cancer, or a history of cancer; in its third edition in 2019, young people from eight different European countries were involved). 32 Although some such initiatives proved successful, others were less so. A national project called SIAMO (Società Italiana Adolescenti con Malattie Onco-ematologiche [Italian Society for Adolescents with Oncohematological Diseases]) was launched in 2014, 33,34 as an extension of the AIEOP Committee on Adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…and "Get a check-up") aimed at helping young people interpret any symptoms they experience, seek medical advice, and arrive at an earlier diagnosis 54 ; and the "Winners' Cup" (a football tournament for adolescents with cancer or a history of cancer that, in its third edition in 2019, involved young people from eight different European countries). 55 A recent survey (conducted in 2020) showed that 19 AIEOP centers have developed specific programs dedicated to adolescent patients (10 years earlier, only two centers had attempted to do so) [56][57][58][59][60][61]. The percentage of adolescents treated at AIEOP centers has also increased over the years, with the observed/expected ratio rising from 10% in 1989-2006 to 28% in 2007-2012, and 37% in 2013-2017.…”
Section: The Italian Programmentioning
confidence: 99%
“…A few examples worth mentioning are as follows: a campaign called “There’s no reason why” (to improve awareness that cancer can develop in adolescence) 53 ; the #fattivedere campaign (an Italian term with the dual meaning of “Don’t hide!” and “Get a check-up”) aimed at helping young people interpret any symptoms they experience, seek medical advice, and arrive at an earlier diagnosis 54 ; and the “Winners’ Cup” (a football tournament for adolescents with cancer or a history of cancer that, in its third edition in 2019, involved young people from eight different European countries). 55…”
Section: The Italian Programmentioning
confidence: 99%
“…4 The AIEOP Adolescents Working Group (former AIEOP Adolescents Committee) initially focused its efforts on improving adolescents' access to AIEOP centers and their inclusion in clinical trials. [5][6][7][8][9][10] Among the various initiatives launched by the AIEOP Adolescents Working Group, examples worth mentioning are: 13 As a major goal, the AIEOP Adolescents Working Group aimed to promote interaction and collaboration with the adult oncology world. With the idea to create a broad-based, national platform dedicated to AYA, a national project called SIAMO (i.e.…”
Section: Introductionmentioning
confidence: 99%